Necroptosis and tumor progression - Yan, Jiong; Wan, Peixing; Choksi, Swati; Liu, Zheng-Gang (Trends in cancer, 2022)
Necroptosis, a form of programmed necrotic cell death, is a gatekeeper of host defense against certain pathogen invasions. The deregulation of necroptosis is also a key factor of many inflammatory diseases. Recent studies have revealed an important role of necroptosis in tumorigenesis and metastasis and imply the potential of targeting necroptosis as a novel cancer therapy. While its molecular mechanism has been well studied, details of the regulation and function of necroptosis of tumor cells in tumorigenesis and metastasis only began to emerge recently, and we discuss these herein.